ФАРҒОНА ВИЛОЯТИ ШАҲАРЛАРИДА АҲОЛИГА ТИББИЙ ХИЗМАТ КЎРСАТИШНИНГ АҲВОЛИ (1917 – 1924 йиллар) (Scientific journal of the Fergana State University, 2023)
This article dedicated  the state and the problems that have taken place in the medical care of the population of  cities of the Ferghana region